The Eeg Spectral Reaction Mapping: An Imagistic Method with Diagnostic Relevance - Psatta , Dan M.; Olaru , Mircea; Matei , Mihaela (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
We evidence in this work an EEG Mapping procedure able to reveal the normal functional mechanisms of the neocortex and their disturbance in pathology. The EEG power of Delta, Theta, Alpha, Beta and th Delta+Theta/ Alpha + Beta power coefficients are compared in prcentages between testing and rest, between 0% and 250% (standard scales). The percentage of 100% denotes the lack of EEG reaction. Thus, Maps may be compared both horizontally (between patients) and lonitudinally (in time). In comparison with MRI, EEG Mapping does not need the use of magetic fields and radio waves, or the injection of a contrast material.